Electrodiagnostic testing in acute facial palsy: Outcomes and comparison of methods - Andresen, Nicholas S. (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: To study the relationship between various electrodiagnostic modalities in acute facial palsy. SETTING: Academic tertiary care center. PATIENTS: One‐hundred and six patients who presented with traumatic or non‐traumatic acute facial paralysis (House‐Brackmann, HB, grade 6/6) between 2008 and 2017 and underwent acute electrodiagnostic testing. INTERVENTION: Electroneurography (ENoG) using nasolabial fold (NLF) or nasalis muscle (NM) methods, and volitional electromyography (EMG) in all patients. MAIN OUTCOME MEASURES: Percent degeneration of ipsilateral facial nerve compound muscle action potentials (CMAP) on NLF‐ and NM‐ENoG, presence or absence of muscle unit potentials (MUPs) on EMG. RESULTS: Extent of facial nerve degeneration measured by NLF‐ and NM‐ENoG were highly correlated (r = 0.85, P < .01) on each test and on serial testing. NLF‐ and NM‐ENoG concordantly diagnosed ≥90% degeneration in 44 patients (80%), of whom 32 patients were diagnosed to have 100% degeneration by both methodologies. Absence of MUPs on EMG was 63% sensitive and 92% specific for ≥90% degeneration on ENoG, with a positive predictive value of 90%. For patients with Bell's palsy, percent degeneration on ENoG was also correlated to HB score at 1 year. Surgical decompression resulted in mean HB scores of 2.2 and 3.0 for patients with Bell's palsy and trauma, respectively. CONCLUSIONS: NM‐ENoG may be a valid and comparable method to NLF‐ENoG for predicting the recovery of facial nerve function in acute paralysis. Absence of MUPs on EMG is a specific measure of severe degeneration and highly predictive of candidacy for surgical decompression. LEVEL OF EVIDENCE: Level 3.